Implementasi dan Manfaat ICE-Breaking pada Proses Pembelajaran di SMP Negeri 11 Pekanbaru - Setiawan Sinaga, Joel; Suryati; Syaflita, Dina (JURNAL ARMADA PENDIDIKAN, 2023)
In the learning process, the teacher's ability to direct students' attention and motivation to learn is tested, especially at the elementary school level, where students do not yet know how to improve themselves, at this level they often do not focus on receiving learning, so students no longer receive attention and motivation. Teachers must understand the psychological state of students in order to create a good, fun and effective learning atmosphere. So that the learning objectives or achievements of the day are realized. One way that can be done to attract students' attention is to apply ice-breakers in learning activities that are used to be able to arouse enthusiasm and also to attract students' attention. the results of the study it can be concluded that the application of the ice breaking strategy can overcome student boredom in the science learning process at SMP Negeri 11 Pekanbaru.